Pembinaan Karakter Anak Melalui Pembelajaran Nilai-Nilai Qur’ani di TK IT Salsabila 2 Yogyakarta - Lisna, Ade (Program Studi Pendidikan Islam Anak Usia Dini, Fakultas Ilmu Tarbiyah dan Keguruan, UIN Sunan Kalijaga Yogyakarta, 2019)
This study aims to determine the character building through learning the values of Qur'an in TK IT SALSABILA 2. The method used in this research is a qualitative method with data collection techniques of observation and interviews. Analysis of the data used is the collection, reduction and verification of data. The results showed that: 1) children routinely deposit memorization every day for two verses, 2) children are responsible for the tasks given. The teacher motivates children to foster children's character in accordance with Qur'anic values. Fostering the character of children in accordance with the expected goals of children being more responsible, disciplined, and trustworthy